Neuronal Degeneration in Mice Induced by an Epidemic Strain of Saint Louis Encephalitis Virus Isolated in Argentina - Rivarola, María E.; de Olmos, Soledad; Albrieu-Llinás, Guillermo; Tauro, Laura B.; Gorosito-Serrán, Melisa; Konigheim, Brenda S.; Contigiani, Marta S.; Gruppi, Adriana (Frontiers in Microbiology, 2018)
Saint Louis encephalitis virus (SLEV) is a neglected flavivirus that causes severe neurological disorders. The epidemic strain of SLEV, CbaAr-4005, isolated during an outbreak in Córdoba city (Argentina), causes meningitis and encephalitis associated with neurological symptoms in a murine experimental model. Here, we identified the affected brain areas and the damage triggered by this neurotropic arbovirus. We performed a detailed analysis of brain neurodegeneration associated with CbaAr-4005 SLEV infection in mice. The motor cortex, corpus striatum and cerebellum were the most affected structures. Neurodegeneration was also found in the olfactory bulb, thalamus, hypothalamus, hippocampus, and hindbrain. SLEV infection triggered brain cell apoptosis as well as somatodendritic and terminal degeneration. In addition, we observed massive excitotoxic-like degeneration in many cortical structures. Apoptosis was also detected in the neuroblastoma cell line N2a cultured with SLEV. The results evidenced that SLEV CbaAr-4005 infection induced severe degenerative alterations within the central nervous system of infected mice, providing new information about the targets of this flavivirus infection.